Influence of Novel Beam Shapes on Laser-Based Processing of High-Strength Aluminium Alloys on the Basis of EN AW-5083 Single Weld Tracks - Nahr, Florian; Bartels, Dominic; Rothfelder, Richard; Schmidt, Michael (Journal of Manufacturing and Materials Processing, 2023)
The commonly used Gaussian intensity distribution during the laser-based processing of metals can negatively affect melt pool stability, which might lead to defects such as porosity, hot cracking, or poor surface quality. Hot cracking is a major factor in limiting production rates of high-strength aluminium alloys in laser-based processes such as welding or the powder bed fusion of metals (PBF-LB/M). Going away from a Gaussian intensity distribution to ring-shaped profiles allows for a more even heat distribution during processing, resulting in more stable melt pools and reduced defect formations. Therefore, the aim of this study is to investigate the influence of different laser beam profiles on the processing of high-strength aluminium alloys by using a multicore fiber laser, allowing for in-house beam shaping. Single weld tracks on the aluminium alloy EN AW-5083 are produced with varying laser powers and weld speeds, as well as different beam profiles, ranging from Gaussian intensity distribution to point/ring profiles. The molten cross sections are analyzed regarding their geometry and defects, and the surface roughness of the weld tracks is measured. By using point/ring beam profiles, the processing window can be significantly increased. Hot cracking is considerably reduced for weld speeds of up to 1000 mm/s compared to the Gaussian beam profile. Furthermore, the melt pool width and depth are more stable, with varying parameters for the point/ring profiles, while the Gaussian beam tends to keyhole formation at higher beam powers. Finally, a strong decrease in surface roughness for the point/ring profiles, accompanied by a significantly reduced humping effect, starting even at lower beam powers of 200 W, can be observed. Therefore, these results show the potential of beam shaping for further applications in laser-based processing of high-strength aluminium alloys<br
Keywords: laser welding; beam shaping; melt pool geometry; hot cracks; surface roughness